Mountainous regions and agricultural policy in Slovenia - Cunder, Tomaž (Economics of Agriculture, 2010)
Due to varied natural conditions, a considerable share of agricultural land in Slovenia is situated in the less favoured areas (LFAs). From the spatial as well as social, agrarian and political points of view they are an essential segment of structural development. The long-term objective of the agricultural and social policy towards the LFAs areas is the preservation of functional ability of these areas. Compensatory allowances considerably contribute to income of farmers in specifc areas. In connection with basic criteria of good farming practice, the measure contributes to preservation of agricultural land as well and therefore improves also the environmental functions of LFAs. The prepared paper briefly outlines theoretical arguments for introducing of EU comparable LFAs policy and examines the implementation of accompanying measures in Slovenian agricultural policy. The paper is based on desk research drawing from responsible literature, legislation documents and available research studies.